2017
DOI: 10.1051/matecconf/201710608024
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Housing Development in Conditions of Changing Living Environment

Abstract: Abstract. Article provides the organization-economic mechanism of sustainable development of the housing, the main content of which is formalized reflection of quality, environmental friendliness and cost of housing stock in conditions of changing living environment. Considered underlying principles of the sustainable development concept and considered experience of the developed countries at formation of the sustainable development of the housing allowed to analyze the main documents in which concept of susta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 6 publications
(4 reference statements)
1
35
0
Order By: Relevance
“…The models, that were developed earlier [8,9] and are currently under development by NIIMosstroy's research staff, will allow to take into account the influence of a number of characteristics on a specific energy consumption of multi-apartment residential buildings: heat input from sunlight during the heating season in Moscow's climate; heat emission from household appliances in a new building with different accomodation density; humidity of external walls and processes, which are related with their drainage, etc. The scientific value and practical significance of the results of the conducted studies is that the obtained data will be tested and confirmed by the results of numerical, laboratory and field experiments and measurements.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…The models, that were developed earlier [8,9] and are currently under development by NIIMosstroy's research staff, will allow to take into account the influence of a number of characteristics on a specific energy consumption of multi-apartment residential buildings: heat input from sunlight during the heating season in Moscow's climate; heat emission from household appliances in a new building with different accomodation density; humidity of external walls and processes, which are related with their drainage, etc. The scientific value and practical significance of the results of the conducted studies is that the obtained data will be tested and confirmed by the results of numerical, laboratory and field experiments and measurements.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Tikhonova [4], the economic status of individuals is determined by the level of income and the possession of property (real estate, durable goods, savings). She rightly asserts that the problem of real estate at the disposal of the population has a special status: 1. this is the most expensive property that citizens have (most of them are not able to buy housing independently); 2. residential real estate is a criterion of well-being, accumulated throughout life, by a specific family; 3. the nature (level) of occupied housing allows one to refer to the rich, and others to the poor [5]. So, regarding housing conditions, this should be housing of different storeys (including high-rise buildings, low-rise buildings, etc.)…”
Section: Methods and Resultsmentioning
confidence: 99%
“…The most effective are adequate legal regulations and the respective restrictions. [6][7][8] The first legal act in Poland which concerned sustainable development was the act of 7 July 1994 on land development. Sustainable development was also defined by the Art.…”
Section: Actions For Sustainable Constructionmentioning
confidence: 99%